Measuring the psychological combustion of the Communicator in Syrian state television channels (Journal of Hama University, 2021)
The worker in media sometimes feels, after years of media work, that he is unable to work as before, and feels what is called psychological combustion, which is known by the media’s feeling of fatigue consumption, and the lack of motivation with his feeling that what he provides is not desirable and unimportant, where the research aims to explore the prevalence of the phenomenon of psychological combustion among the communicators in the Syrian government TV channels and to identify the relationship of psychological combustion with Some demographic variables of the communicator and includes (type- experience) and a Maslak measure of psychological combustion has been applied On a sample of 50 individuals in the Syrian government TV channels, the descriptive and analytical approach was adopted.The results of the research showed that the communicator on Syrian state television channels suffers from psychological combustion at high levels.